2023
DOI: 10.3390/axioms12060536
|View full text |Cite
|
Sign up to set email alerts
|

A Mathematical Analysis of the Stress Statement of the Soil Basis under Complex Loading near the Retaining Wall

Abstract: The present paper describes and provides an analytical solution to the problem of the stress state of a limited-thickness soil basis resting on an incompressible soil base, under the action of two distributed loads of different intensities near the retaining wall of an excavation pit. It is proposed that the method for identifying components of the stress statement within the framework of the engineering problem in question is improved, and the solution is based on the trigonometric Ribiere–Fileon series. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
0
0
Order By: Relevance
“…Ter-Martirosyan and Vanina [24] analyzed the effect of the load from stockpiled materials and construction machinery near the edge of a rectangular retaining wall on a soil foundation resting on an incompressible base. Their analyses indicated that the displacement of horizontal stresses toward a retaining wall results in extra internal forces in the retaining wall, which should be considered for reinforcing concrete retaining walls.…”
Section: Introductionmentioning
confidence: 99%
“…Ter-Martirosyan and Vanina [24] analyzed the effect of the load from stockpiled materials and construction machinery near the edge of a rectangular retaining wall on a soil foundation resting on an incompressible base. Their analyses indicated that the displacement of horizontal stresses toward a retaining wall results in extra internal forces in the retaining wall, which should be considered for reinforcing concrete retaining walls.…”
Section: Introductionmentioning
confidence: 99%